Passive Islamophobia and cultural national construction: a critical note on art curriculum - Saifuddin Dhuhri; Hamka Hasan; Ahmad Sholeh Sakni; Iffatul Umniati Ismail (IAIN Salatiga, 2021)
This study aims to explore the passive Islamophobia in the arts and culture subjects on the KTSP and K-13 curriculum of secondary schools. Employing the representation theory, this article explores the relationship between marginality and Islamophobia integrated into the fine arts curriculum. Through content analysis of 2 textbooks for grades VII and VIII, some elements of marginalization in the Islamic cultural values were found. The conception of Indonesian nationality originates from various internal solidarity and contestation between Islamism, Hinduism and secularism in resistance to imperialism. The fallacy in the narrative of the mainstream of Indonesian nationalism seen as deeply rooted in the legacy of Majapahit/Hinduism, which unwittingly calls Indonesia the new Majapahit needs to be straightened out. The construction of cultural nationalism, meanwhile, overrides Islamic culture and identity. This article indicates that the teaching of the nationality of Indonesian culture does not consider the heritage of Islamic arts and culture. The marginality and exclusion of Islamic arts and culture in the construction of Indonesian nationality through the art curriculum and art education policy shows passive Islamophobia internalized therein, instead of the existence of accommodation and respect for Islamic culture.